Ahmet Rıza Bey's Early Ideas (1892-1895) - Ömer Avcı (Türkiyat Mecmuası)
Ahmet Rıza Bey was an intellect and activist who guided Turkish modernization history through his ideas and political activities. His family also had significant roles in the high bureaucracy of the state. Ahmet Rıza Bey’s worldview was shaped by the modern philosophical movement of positivism, with the mottos of order and progress being key concepts in his ideas. The purpose of this article is to shed light on the intellectual background of Ahmet Rıza Bey’s early writings known as the Birinci Lâyiha [First Memorandum], Dil Akademisi Lâyihası [Language Academy Memorandum], and Mektub [Letter]. In this sense, no comparisons have yet been made between Ahmet Rıza Bey’s reports and those written by the Ottoman statesmen and intellectuals of the period. This article emphasizes the secular contexts of the topics Ahmet Rıza Bey addressed through a textual content analysis and literature review. These texts are unique examples in terms of being confined to the positivist doctrine in their ideological orientation. These texts were also conditioned to explain the rationale and method of an effort focused on saving the empire through education. His writings emphasized how reforms should be implemented gradually and within historical continuity by highlighting the importance of political and social stability. In this respect, he aimed to give public identities to the concepts symbolized as science, work, order, progress, morality, and education that shaped Turkish modernization history. Ahmet Rıza Bey’s early writings saw the concept of order as the focal point of reform proposals, with the concept of progress being a variable dependent on the concept of order. Therefore, Ahmet Rıza Bey had favored the continuation of the Ottoman monarchy over a radical regime change. He grounded his understanding of change not so much on the political level but on the establishment of a holistic and solidarity-based collective consciousness.